2007
DOI: 10.1016/j.vetmic.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of bovine noroviruses in South Korea

Abstract: Since the prevalence of bovine norovirus (BNoV) and their genetic diversity have only been reported in the USA, England, Germany and The Netherlands, this study examined the prevalence and genetic diversity of BNoVs in diarrheic calves in South Korea using 645 diarrheic fecal specimens from calves by RT-PCR and nested PCR assays. Overall, 9.3% of the diarrheic fecal samples tested positive for BNoVs by either RT-PCR or nested PCR, of which 5.9% samples also tested positive for other enteric pathogens including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
43
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
(52 reference statements)
12
43
1
2
Order By: Relevance
“…The molecular prevalence of BoNoV in samples coming from the Belgian diagnostic laboratory was in accordance with studies in Great Britain (Milnes et al, 2007) and Korea where Park et al (2007) report also a majority of genotype 2 infection. The genotype of the strains detected in the British study was not clarified.…”
Section: Discussionsupporting
confidence: 87%
“…The molecular prevalence of BoNoV in samples coming from the Belgian diagnostic laboratory was in accordance with studies in Great Britain (Milnes et al, 2007) and Korea where Park et al (2007) report also a majority of genotype 2 infection. The genotype of the strains detected in the British study was not clarified.…”
Section: Discussionsupporting
confidence: 87%
“…The specific etiology of many field cases of calf diarrhea still remain undiagnosed (Milnes et al, 2007). Recently, bovine norovirus (BNoV), Nebovirus, bovine enterovirus (BEV) and bovine torovirus (BToV) have been identified as potential causes of calf diarrhea (Blas-Machado et al, 2007;Haschek et al, 2006;Hoet et al, 2003a;Kaplon et al, 2011;Otto et al, 2011;Park et al, 2007Park et al, , 2008a. Some of these agents (i.e., BNoV, BEV and BToV) have also been found in feces from clinically healthy calves (Haschek et al, 2006;Jimenez-Clavero et al, 2005;Mijovski et al, 2010;Shanks et al, 2008) and many of previous epidemiological studies for BNoV and BToV have been focused only on diarrheic calves (Hoet et al, 2003b;Milnes et al, 2007;Park et al, 2007Park et al, , 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, most of the available information about torovirus epidemiology has been obtained from bovine torovirus (BToV), since successful experimental infections of gnotobiotic calves can be readily performed, and this, in turn, has facilitated the development of diagnostic methods to detect antibodies in serum samples (Brown et al, 1987) and viral particles in faecal specimens (Koopmans et al, 1990). BToV was first isolated in United States (Woode et al, 1982), but it has been later found in other countries such as Canada (Duckmanton et al, 1998), Japan (Ito et al, 2007), South Korea (Park et al, 2007), Austria (Haschek et al, 2006), United Kingdom (Liebler et al, 1992), The Netherlands (Koopmans et al, 1989), Germany (Koop-mans et al, 1989), Italy (Lavazza, 1989) and South Africa (Vorster and Gerdes, 1993). Moreover, the infectious cycle of BToV under natural field conditions was established by compiling information from different studies (Hoet and Saif, 2004).…”
Section: Introductionmentioning
confidence: 99%